Bold Followership A Biblical Cure for Organizational Toxicity - Buford, Maurice A. (Christian Faith Perspectives in Leadership and Business, 2018)
This book uses biblical writings to examine how to to build wise and moral boardroom boldness to mitigate executive ethical mishaps. The author uses the story of King David to explore the possible perplexities followers experience when their leaders suddenly make a toxic choice. Introducing a boardroom boldness language model (BBLM), Buford presents five boardroom language to use when dealing with toxic leaders. How well organizations brace, respond, and proactively navigate the uncharted terrain of uncertainty could play a pivotal role in the success of the firm. Calling into question traditional constructs affiliated with power and trust, this book will advance the greater discussion by integrating spirituality, case studies, and leadership principles to measure the culture to cultivate boardroom boldness.